Association between culture and the preference for, and perceptions of, 11 routes of medicine administration: A survey in 21 countries and regions - Sudaxshina Murdan; Li Wei; Diana A. van Riet-Nales; Abyot Endale Gurmu; Stella Folajole Usifoh; Adriana-Elena Tăerel; Ayca Yıldız-Peköz; Dušanka Krajnović; Lilian M. Azzopardi; Tina Brock; Ana I. Fernandes; André Luis Souza dos Santos; et al. (Elsevier, 2023)
Medicines can be taken by various routes of administration. These can impact the effects and perceptions of medicines. The literature about individuals' preferences for and perceptions of the different routes of administration is sparse, but indicates a potential influence of culture. Our aim was to determine: (i) any association between one's culture and one's preferred route of medicine administration and (ii) individual perceptions of pain, efficacy, speed of action and acceptability when medicines are swallowed or placed in the mouth, under the tongue, in the nose, eye, ear, lungs, rectum, vagina, on the skin, or areinjected.A cross-sectional, questionnaire-based survey of adults was conducted in 21 countries and regions of the world, namely, Tunisia, Ghana, Nigeria, Turkey, Ethiopia, Lebanon, Malta, Brazil, Great Britain, United States, India, Serbia, Romania, Portugal, France, Netherlands, Japan, South Korea, Hong Kong, mainland China and Estonia, using the Inglehart-Welzel cultural map to ensure coverage across all cultures. Participants scored the pain/discomfort, efficacy, speed of onset and acceptability of the different routes of medicine administration and stated their preferred route. Demographic information was collected.A total of 4435 participants took part in the survey. Overall, the oral route was the most preferred route, followed by injection, while the rectal route was the least preferred. While the oral route was the most preferred in all cultures, the percentage of participants selecting this route varied, from 98% in Protestant Europe to 50% in the African-Islamic culture. A multinomial logistic regression model revealed a number of predictors for the preferred route. Injections were favoured in the Baltic, South Asia, Latin America and African-Islamic cultures while dermal administration was favoured in Catholic Europe, Baltic and Latin America cultures. A marked association was found between culture and the preference for, and perceptions of the different routes by which medicines are taken. This applied to even the least favoured routes (vaginal and rectal). Only women were asked about the vaginal route, and our data shows that the vaginal route was slightly more popular than the rectal one.